Leaf and stem anatomy of Vochysiaceae in relation to subfamilial and suprafamilial systematics - Sajo, M. G. [UNESP]; Rudall, P. J. (Oxford University Press (OUP), 2002)
Several leaf anatomical features are potentially systematically informative within both the family Vochysiaceae and the order Myrtales, notably tracheoidal idioblasts, mucilage cells and secretory canals. Tracheoids with spiral wall thickenings are present in the mesophyll of most species of Vochysia, and also occur in several other families of Myrtales. Mucilage cells are common in the leaf epidermis in some Vochysiaceae. Secretory ducts are present in the midrib in Salvertia and Vochysia, which are apparently closely related, although Salvertia also shares some leaf anatomical characters with Qualea and Callisthene. Anatomical data do not support the segregation of Ruizterania from Qualea; leaves of R. albiflora leaves are very similar to those of Q. paraensis in venation pattern, and leaf and stem anatomy. Different venation patterns are characteristic of sections within the genus Qualea, but within the large genus Vochysia, leaf anatomy is variable even within a subsection. Amongst other Myrtales, leaf anatomy of Vochysiaceae most closely resembles that of Combretaceae and Onagraceae. © 2002 The Linnean Society of London.
Keywords: Mucilage cells; Myrtales; Neotropics; Secretory ducts; Vasculature; Venation; anatomy; Callisthene; Combretaceae; Onagraceae; Qualea; Ruizterania; Salvertia; Vochysia; Vochysiaceae